The Association between Coagulation Parameters, C-Reactive Protein, D-Dimer and In-Hospital Mortality of Covid-19 Patients with Suspected Pulmonary Embolism - Delmi, Anwari; Adiputro, Dwi Laksono; Nurrasyidah, Ira; Yasmina, Alfi (Berkala Kedokteran, 2024)
COVID-19 is a respiratory disease with severe cardiovascular complications, one of them is pulmonary embolism (PE). Studies have shown many contributing factors related to mortality of hospitalized COVID-19 patients that developed pulmonary embolism. This study aimed to find the association between coagulation parameters (PT and APTT), C-reactive protein (CRP), and D-dimer with in-hospital mortality of COVID-19 patients with suspected PE. COVID-19 patients in Ulin General Hospital Banjarmasin who met the clinical criteria of suspected PE, assessed with clinical scorings (Well’s score for PE and Padua prediction score for venous thromboembolism), and receiving anticoagulant therapy recorded in medical records were included in this study. A total of 91 patients were included, with most patients were female (59.3%), average age of 53.36 years, average BMI of 25.82 kg/m2, having normal electrocardiogram (79.1%), with history of hypertension (56%), and no histories of smoking (94.5%), diabetes mellitus (70.3%), heart failure (93.4%), coronary artery disease (96.7%), and chronic lung disease (95.6%).  As much as 39.57% patients with suspected PE was deceased during the course of hospitalization. Unadjusted analysis showed significant increased levels of PT, APTT, and CRP, in deceased patients compared to those discharged alive (mean 14.62 vs 11.91 seconds, 42.94 vs 28.57 seconds, and 98.19 vs 47.01 mg/dL, respectively; p value < 0.01), and a non-significant increased level of D-dimer (mean 10.89 mg/L; p = 0.09). Multivariate logistic regression showed non-significant associations between PT, APTT, D-dimer, and CRP with in-hospital mortality (p values of 0.06, 0.14, 0.52, and 0.23, respectively). In conclusion, there is no association between coagulation parameters, CRP, and D-dimer levels with in-hospital mortality in COVID-19 patients with suspected PE.  A further study with a larger sample size is needed to see the role of laboratory findings in predicting in-hospital mortality in COVID-19 patients with suspected PE.